GAMBARAN MOTIVASI REMAJA SOCIAL WITHDRAWAL PADA USIA SEKOLAH MENENGAH PERTAMA - Astria Kasih; Adang Hambali (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2013)
Social withdrawal is behavior among teenager in which they withdraw because of nonfearful aspects and dysregulation. Having qualitative method, this research had case study with descriptive study. Collecting data used observation, interview ad documentation. Case study analysis shows that there is dysregulation emotional aspects related to fear, anxiety, and shame. Result indicate some factors affecting social withdraw on children at school age which are parents, family, and environment.